Do body-worn cameras reduce eyewitness cooperation with the police? An experimental inquiry - Hamm, J. A. (Journal of experimental criminology, 2019)
The current research adds to the literature addressing police body-worn cameras (BWCs) by experimentally evaluating their effect on an interaction that has, to date, received relatively little systematic, empirical attention: police-eyewitness interactions. Although research suggests that BWCs generally have positive effects, legal scholars and media professionals have long argued that deploying cameras in this context may backfire, especially by chilling public willingness to speak with police.